2003
DOI: 10.1063/1.1561619
|View full text |Cite
|
Sign up to set email alerts
|

Photodissociation of vibrationally excited ammonia: Rotational excitation in the NH2 product

Abstract: Three-center versus four-center elimination in photolysis of vinyl fluoride and vinyl bromide at 193 nm: Bimodal rotational distribution of HF and HBr (v5) detected with time-resolved Fourier transform spectroscopy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 12 publications
2
24
0
Order By: Relevance
“…[35][36][37] For this reason we have used, 29,30 and use here, the 1,2 1 A states of NH 3 as our test case.…”
Section: Application To the 12 1 A States Of Nhmentioning
confidence: 99%
See 1 more Smart Citation
“…[35][36][37] For this reason we have used, 29,30 and use here, the 1,2 1 A states of NH 3 as our test case.…”
Section: Application To the 12 1 A States Of Nhmentioning
confidence: 99%
“…This H d represents a significant improvement of that determined in P1 and P2 where the domain was determined largely through chemical intuition. Section III describes the ab initio treatment of, and the H d used to describe, the 1,2 1 A states of NH 3 which have been used in our previous work on quasi-diabatic representations, and provide an archetypical system for nonadiabatic dynamics involving conical intersections, [32][33][34] of considerable current experimental [35][36][37] and theoretical [38][39][40][41][42][43] interest. Section IV describes the performance of H d .…”
Section: Introductionmentioning
confidence: 99%
“…Detailed measurements of the absorption spectra, 4-12 product internal state distributions, [13][14][15][16][17][18][19][20][21][22][23][24][25] and dissociation lifetimes 26,27 have been reported. Particularly relevant to the a) Authors to whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…28,29 Strong mode and bond selectivity has been found. 24,[30][31][32][33][34][35][36][37] One of the most intriguing findings in the vibrationally mediated ammonia photodissociation is the strong mode selectivity of the NH 2 (Ã 2 A 1 )/NH 2 (X 2 B 1 ) branching ratio. 34,37 Unlike the commonly observed dominance of the ground state NH 2 (X 2 B 1 ) channel, excitation in the antisymmetric stretching mode of NH 3 prior to photolysis resulted in mostly adiabatic dissociation to NH 2 (Ã 2 A 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…The dynamics of photoexcited ammonia has been experimentally investigated by several research groups, [30][31][32][33][34][35][36][37][38][39][40][41][42] of which we single out two. [30][31][32]43,44 Biesner et al 30 studied the effect of excitation of the umbrella mode and found that NH 2 fragments were highly rotationally excited when n 2 = 0, where n 2 is the number of umbrella-mode quanta initially in vibration, and nonadiabatic dynamics, presumed to be due to passage through or near the conical intersection, was favored. For larger n 2 values the situation became harder to interpret due to the increase in electronically and vibrationally excited products.…”
Section: Introductionmentioning
confidence: 99%